THE RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND ADOLESCENT ATTITUDES ABOUT HIV/AIDS TOWARDS PREMARITAL SEXUAL BEHAVIOR IN HIGH SCHOOL STUDENTS IN SERANG CITY - Ikhlasiah, Marthia; Prihayati; Ismarina; Lathifah, Dinah (ZILLZELL MEDIA PRIMA, 2023)
Lack of knowledge and attitudes about HIV/AIDS towards premarital sexual behavior results in the birth of a generation with HIV/AIDS. Adolescents who have deviations from sexual behavior that cause high rates of HIV/AIDS can lead to poor quality of life and low human resources (HR) in the country. The purpose of this study was to determine the relationship between the level of knowledge and attitudes of adolescents about HIV/AIDS towards premarital sexual behavior in class XI students at SMAN 5 Serang City in 2023. The research design was correlative analytic with a cross sectional survey time approach. The sample was calculated using the slovin calculation formula as many as 110 respondents from a total population of 258 class XI students. The sampling technique is non-probability sampling using purposive sampling according to the consideration of the researcher. The data collection tool uses a questionnaire that has been tested for validity and reliability from previous researchers and modified into